Analysis of a Court Ruling on Criminal Sanctions for a Minor Perpetrator of Rape (Study of Court Ruling No. 70/Pid. Sus-Anak/2024/PN Medan) - Cindi Patricia Surbakti; Abdul Rahman Maulana Siregar; Aulia Rahman Hakim Hasibuan (CV. Era Digital Nusantara, 2026)
This study discusses legal considerations regarding criminal sanctions and work training for children as perpetrators of sexual intercourse crimes, focusing on Medan District Court Decision Number 70/pid.sus Anak/2024/PN Medan as the source case. This is done to ensure that children in conflict with the law continue to receive supportive care for future guidance and rehabilitation. Conversely, children can also be criminalized. Therefore, the issues discussed include the legal basis governing the criminal responsibility of children towards children and the considerations taken by judges when they make decisions after being found guilty by a judge in accordance with Article 81 Paragraph (2) Article 76d of the Child Criminal Justice System Law (SPPA Law). This study uses a normative juridical method with a case study approach, examining materials from secondary and tertiary law, literature reviews, and descriptive analysis. This study also focuses on providing recovery to victims to achieve a more balanced justice in the Juvenile Criminal Justice System in Indonesia. The results of the study show that the judge's considerations include legal aspects such as (UU SPPA). However, the considerations in the verdict are inaccurate because they do not pay enough attention to the future of the victims..